2008
DOI: 10.1002/ibd.20347
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarkers in a mouse model of bacterial-induced inflammatory bowel disease

Abstract: Serum analyte measurement is a useful, noninvasive method for monitoring disease in a mouse model of bacterial-induced IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…In the present study, we observed that plasma levels of MMP-9 but not MMP-2 were increased early in abdominal sepsis. This observation is in line with other studies reporting that MMP-9 levels are elevated in the circulation of infectious disease models [40,41]. We next investigated whether MMP-9 might be involved in platelet shedding of CD40L in sepsis.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we observed that plasma levels of MMP-9 but not MMP-2 were increased early in abdominal sepsis. This observation is in line with other studies reporting that MMP-9 levels are elevated in the circulation of infectious disease models [40,41]. We next investigated whether MMP-9 might be involved in platelet shedding of CD40L in sepsis.…”
Section: Discussionsupporting
confidence: 90%
“…10 Using both ELISA and western blot, we observed herein that plasma levels of MMP-9 were increased in abdominal sepsis. This finding is in accordance with other investigations showing enhanced MMP-9 levels in the circulation of sepsis and infectious disease models, [37][38][39] as well as in patients with sepsis. 10,40 Notably, it was observed that administration of NSC23766 significantly decreased the sepsis-induced increase of MMP-9 levels in plasma, indicating that Rac1 might be an important regulator of systemic levels of MMP-9 in abdominal sepsis.…”
Section: Discussionsupporting
confidence: 82%
“…Previous clinical and animal studies have demonstrated that the lymphotactin-XCR interaction contributes in the pathogenesis of inflammatory diseases, including rheumatoid arthritis, systemic sclerosis, inflammatory bowel disease, glomerulonephritis and HIV infection [17][18][19][20][21][22]. In the eye, upregulation of lymphotactin expression is found in the mouse cornea after mechanical trauma or endotoxin exposure, and may be related to early corneal graft rejection [23].…”
Section: Introductionmentioning
confidence: 98%